2014
DOI: 10.1007/s11010-014-1995-5
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CYP1A1, CYP1A2, CYP1B1, increased oxidative stress and inflammation in the lung and liver tissues of rats exposed to incense smoke

Abstract: Incense smoke is increasingly being recognized as a potential environmental contaminant and is linked to malignant and non-malignant respiratory diseases. The detoxification of environmental contaminants including polycyclic aromatic hydrocarbons (PAHs) involves the induction of cytochrome P-450 family enzymes (CYPs) by PAHs. However, the detoxification of PAHs also results in the generation of reactive and unstable intermediary metabolites which are implicated in the oxidative stress, DNA damage, and inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 48 publications
4
68
0
1
Order By: Relevance
“…CS exposure is linked to the increased CYP1A1/CYP1B1 activity (Hukkanen et al, 2002;Hussain et al, 2014). However, our results indicated that the prominent 3R4F (0.25)-induced toxicity (thinning of the nasal epithelium cultures and increased cytotoxicity level) also impacted the metabolic capacity of the cultures, i.e., the capacity to metabolize nitrosamines and polycyclic aromatic hydrocarbons, which are abundant in CS, via CYP1A1 and CYP1B1 (Hukkanen et al, 2002).…”
Section: Discussionmentioning
confidence: 66%
“…CS exposure is linked to the increased CYP1A1/CYP1B1 activity (Hukkanen et al, 2002;Hussain et al, 2014). However, our results indicated that the prominent 3R4F (0.25)-induced toxicity (thinning of the nasal epithelium cultures and increased cytotoxicity level) also impacted the metabolic capacity of the cultures, i.e., the capacity to metabolize nitrosamines and polycyclic aromatic hydrocarbons, which are abundant in CS, via CYP1A1 and CYP1B1 (Hukkanen et al, 2002).…”
Section: Discussionmentioning
confidence: 66%
“…However, both studies showed decreased plasma testosterone levels. In contrast, chronic exposure resulted in increased levels of oxidative stress and inflammation markers, as well as marked ultrastructural changes in the heart muscle (Al-Attas et al, 2015;Alokail et al, 2011;Hussain et al, 2014). Considering the potential health risks of the emission from agarwood smoke, more refined studies are warranted to ensure the safety of indoor agarwood burning for human health.…”
Section: Toxicity and Safetymentioning
confidence: 99%
“…Nevertheless, aryl hydrocarbon hydroxylase activity can be induced up to 15-fold in rat lung by treatment with 3-methylcholanthrene (Matsubara et al, 1974) and its induction is associated with exposure-related mitochondrial dysfunction (Bansal et al, 2014). The inducible aryl hydrocarbon hydroxylase activity of the lung may be particularly important in the formation of carcinogens from cigarette smoke components, and polymorphisms in these enzymes may be a risk factor for the development of lung cancer (Hussain et al, 2014;Hussein et al, 2014;Kim et al, 2004). The lung-specific activity for metabolism of some inhaled agents, particularly benzene and pxylene, exceeds the activity in the liver (Philpot and Smith, 1984) and is critical to the bioactivation of a range of pulmonary toxicants (Kartha and Yost, 2008).…”
Section: Cytochrome-p450 Monooxygenasesmentioning
confidence: 99%